A method for evaluating the granulation effect of sintering mixture
By detecting the particle size composition of the sintered mixture and calculating the relevant index, a systematic method for evaluating the granulation effect of sintered mixture is provided, which solves the problem of imperfect evaluation in the prior art, and achieves high-quality granulation effect and sintering Improved production efficiency.
Patent Information
- Application Number
- CN202410632752.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-05-21
AI Technical Summary
The evaluation method for the granulation effect of sintered mixture in the prior art is not systematic and perfect enough, which makes it difficult to improve the quality of subsequent sintered ores.
Provide a method for evaluating the granulation effect of sintered mixture, including detecting the particle size composition before and after granulation, calculating the average particle size, obtaining the particle growth index, particle distribution index, particle breakage index and depowder rate, and distinguishing it Coefficients determine the granulation effect.
This method can deeply analyze the particle size distribution status and particle strength after granulation, achieve a complete and comprehensive granulation effect evaluation, improve the granulation effect, and improve the yield and efficiency of the sintering machine.
Smart Images

Figure CN118424981B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to an evaluation method for granulation effect of sintering mixture. Background Art
[0002] In the sintering production process, enhancing the permeability of the sintering material layer is the most effective way to improve the productivity of the sintering machine, and the granulation effect of the sintering mixture has a decisive influence on the original permeability of the material layer and the permeability of the sintering process. Therefore, the granulation of the sintering mixture has become an important process in modern sintering production.
[0003] The granulation of sintered mixture is the process of coating finer materials (adhesive powder) onto coarse particles (core particles). The granulated materials are generally called quasi-particles. There are three main factors that control the adhesive particle layer outside the core particles: the core structure (surface state, porosity), moisture content and the total amount of fine powder particles. Adhesive powder is generally less than 0.5mm, core particles are generally larger than 1.0mm, and intermediate particles of 0.5-1.0mm are difficult to granulate.
[0004] The granulation of sintering mixture is usually carried out by a drum granulator. Its working principle is: a powdered mixture with significant particle size distribution characteristics is added to a rolling drum. Under certain humidity conditions, the powder gradually forms particles through the physical action inside the drum. The size and density of the particles can be controlled by adjusting the working parameters of the drum, the humidity of the mixture and other conditions.
[0005] High-quality granulation can significantly improve the quality of sintered ore, increase the output and efficiency of sintering machines, and reduce energy consumption. However, the current evaluation method for the granulation effect of sintering mixtures is not systematic and complete, which makes it difficult to improve the quality of subsequent sintered ore. Summary of the invention
[0006] Based on this, it is necessary to provide a more complete and accurate evaluation method for the granulation effect of sintering mixtures.
[0007] A method for evaluating the granulation effect of a sintering mixture comprises the following steps:
[0008] Provide a sintering mixture, detect the particle size composition of the sintering mixture before granulation, and calculate the average particle size AS0 before granulation according to the particle size composition before granulation; the particle size composition includes a mass percentage M of a particle size greater than 8 mm +8 , Mass percentage of 5-8 mm particle size M 5-8 , mass percentage of 3-5 mm particle size M 3-5 , mass percentage of 1-3 mm particle size M 1-3 , mass percentage of 0.5~1mm particle size M 0.5-1 And the mass percentage of particles less than 0.5 mm M-0.5 ;
[0009] The sintered mixture is granulated, the particle size composition of the sintered mixture after granulation is detected, and the average particle size AS1 after granulation is calculated according to the particle size composition after granulation;
[0010] According to the formula Obtain the particle growth index G of the sintering mixture according to the formula Get the particle distribution index U of the sintering mixture 3-8 ;
[0011] The granulated sintered mixture is subjected to a drop test and a drying test respectively, the particle size composition of the sintered mixture after the drop test and the particle size composition after the drying test are detected, and the average particle size AS3 after the drop test is calculated according to the particle size composition after the drop test;
[0012] According to the formula Obtain the particle damage index D of the sintered mixture according to the formula D 落下 =(M after granulation 3-5 -After drop test M 3-5 )+(M after granulation 5-8 -After drop test M 5-8 )+(M after granulation +8 -After drop test M +8 ) Obtain the powder loss rate D of the sintering mixture 落下 , according to formula D 干燥 =(M after granulation 3-5 -After drying test M 3-5 )+(M after granulation 5-8 -After drying test M 5-8 )+(M after granulation +8 -After drying test M +8 ) Obtain the drying powder removal rate D of the sintering mixture 干燥 ;
[0013] According to the formula Get the discrimination coefficient R; if R≤0.21, it means that the granulation effect is poor; if R>0.21, the particle growth index G and particle distribution index U 3-8 Positively correlated with the granulation effect, particle breakage index D, falling powder loss rate D 落下 , Drying powder removal rate D 干燥 Negatively correlated with granulation effect.
[0014] In one embodiment, the granulation is performed using a drum granulator.
[0015] In one embodiment, a circular baffle plate capable of moving along the axial direction of the cylinder is provided in the cylinder of the cylindrical granulator, the outer diameter of the circular baffle plate is consistent with the inner diameter of the cylinder, the inner diameter of the circular baffle plate is 25% to 33% of the outer diameter, and a granulation space is provided between one side of the circular baffle plate and the cylinder.
[0016] In one of the embodiments, the step of further comprising the following steps before granulation: adjusting the size of the granulation space by moving the annular baffle along the axial direction of the cylinder, and adjusting the amount of sintering mixture added according to the size of the granulation space.
[0017] In one embodiment, the diameter of the cylinder is 400 mm to 1000 mm, and the length is 700 mm to 3000 mm.
[0018] In one embodiment, the drop test includes the following steps: taking the granulated sintered mixture, dropping it from a pipe at a height of 2 m onto a steel plate with a thickness of 10 mm, and repeating the drop for more than 3 times.
[0019] In one embodiment, the drying test includes the following steps: taking the granulated sintered mixture and drying it at a preset furnace temperature and a preset wind speed for a preset time.
[0020] In one of the embodiments, the particle size composition detection includes the following steps: taking the sintered mixture, sieving it with a set of sieves consisting of 8mm, 5mm, 3mm, 1mm, and 0.5mm, then weighing them respectively according to the particle size fraction, and calculating the mass percentage of each particle size fraction.
[0021] In one embodiment, the calculation formula of the average particle size is:
[0022] In one embodiment, the sintering mixture is an iron ore sintering mixture.
[0023] The above solution of the present invention has the following beneficial effects:
[0024] The evaluation method for the granulation effect of the sintering mixture provided by the present invention can deeply analyze the particle size distribution state and particle strength of the mixture after granulation, and realize a complete and comprehensive granulation effect evaluation from representative index detection and analysis calculation, thereby driving the high-quality improvement of the granulation effect and improving the output and efficiency of the sintering machine. The evaluation method is relatively complete and targeted, and the evaluation results are highly representative. It can accurately realize the systematic evaluation of the granulation effect of the sintering mixture, and then guide the stability of the mixture granulation system and the adjustment of process parameters, optimize the operation of the sintering system, and finally improve the sintering production efficiency and quality.
[0025] The present invention adds a circular baffle inside the cylindrical granulator, which can adjust the axial length of the cylinder while keeping the cylinder diameter unchanged, thereby ensuring an effective particle movement form and effectively reducing the amount of sintering mixture. In addition, when the amount of sintering mixture is low, the sample sampled for testing accounts for a larger proportion of the total sintering mixture, and even the entire sintering mixture can be taken for testing. Under the condition of not changing the granulation effect, a test result that can accurately reflect the granulation effect of the sintering mixture with a lower dosage is obtained, which greatly reduces the granulation workload and can achieve a separate evaluation of the granulation effect of the mixture. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the material mixing state in the drum granulator;
[0027] Figure 2 It is a structural schematic diagram of a drum granulator in one embodiment of the present invention;
[0028] Figure 3 It is a cross-sectional view of a drum granulator in one embodiment of the present invention. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. Unless otherwise defined, all professional terms used below have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0032] The ideal particle size distribution can ensure the air permeability and permeability during the sintering process, which is beneficial to improve the sintering efficiency and quality. It is usually necessary to evaluate the average size of the particles and the ratio of fine particles to coarse particles. The strength of the particles is usually evaluated by crushing strength or wear resistance. The granulated particles should have sufficient physical strength to withstand the mechanical stress during subsequent transportation, storage and sintering. The ideal granulated particles should also have appropriate porosity to ensure good gas flow and chemical reaction rate. It is usually necessary to evaluate the density and permeability of the particles. However, the current evaluation method for the granulation effect of sintering mixtures is not systematic and complete. Sintering production usually only evaluates the granulation moisture, bulk density and permeability index of the mixture after granulation. There are few evaluation methods for the particle size structure and particle strength of the mixture.
[0033] In view of the existing problems, the present invention provides a method for evaluating the granulation effect of a sintering mixture, which comprises the following steps:
[0034] S1. Provide a sintering mixture, detect the particle size composition of the sintering mixture before granulation, and calculate the average particle size AS0 before granulation according to the particle size composition before granulation;
[0035] The particle size composition includes the mass percentage of particles larger than 8 mm. +8 , Mass percentage of 5-8mm particle size M 5-8 , mass percentage of 3-5 mm particle size M 3-5 , mass percentage of 1-3 mm particle size M 1-3 , mass percentage of 0.5~1mm particle size M 0.5-1 And the mass percentage of particle size less than 0.5 mm M -0.5 ;
[0036] S2, granulating the sintered mixture, detecting the particle size composition of the sintered mixture after granulation, and calculating the average particle size AS1 after granulation according to the particle size composition after granulation;
[0037] S3, according to the formula Obtain the particle growth index G of the sintering mixture according to the formula Get the particle distribution index U of the sintering mixture 3-8 ;
[0038] S4, subjecting the granulated sintered mixture to a drop test and a drying test respectively, detecting the particle size composition of the sintered mixture after the drop test and the particle size composition after the drying test, and calculating the average particle size AS3 after the drop test according to the particle size composition after the drop test;
[0039] S5. According to the formula Obtain the particle damage index D of the sintered mixture according to the formula D 落下=(M after granulation 3-5 -After drop test M 3-5 )+(M after granulation 5-8 -After drop test M 5-8 )+(M after granulation +8 -After drop test M +8 ) Obtain the powder removal rate D of the sintering mixture 落下 , according to formula D 干燥 =(M after granulation 3-5 -After drying test M 3-5 )+(M after granulation 5-8 -After drying test M 5-8 )+(M after granulation +8 -After drying test M +8 ) Obtain the drying powder removal rate D of the sintering mixture 干燥 ;
[0040] S6. According to the formula Get the discrimination coefficient R;
[0041] If R≤0.21, it means that the granulation effect is poor; if R>0.21, the particle growth index G and particle distribution index U 3-8 Positively correlated with the granulation effect, particle breakage index D, falling powder loss rate D 落下 , Drying powder removal rate D 干燥 Negatively correlated with granulation effect.
[0042] The particle growth index G is used to evaluate the ability of the adhesion powder to wrap around the surface of the core particle so that the core particle grows. The larger the value, the stronger the adhesion powder aggregation ability. 3-8 It is used to evaluate the ability of 3-8mm particles to be concentrated in the granulation quasi-particles. The larger the value, the higher the proportion of quasi-particles distributed in the 3-8mm particle size range, which is more conducive to improving the air permeability of the material layer. The particle breakage index D is used to evaluate the ability of granulation quasi-particles to resist impact during transportation. The smaller the value, the stronger the impact resistance of the granulation raw material. 落下 It is to better evaluate the drop strength of the granulated material and measure the shedding of the adhered powder from the spherical core structure particles during the falling process. The larger the value, the weaker the granulated material's ability to resist the falling impact. 干燥 It is used to evaluate the adhesion strength of intermediate particles. During the granulation process, when the moisture content increases, the intermediate particles stick together into coarse spherical cores, but they will disperse again when drying. The higher the value, the weaker the granulation material's ability to resist thermal shock.
[0043] The discrimination coefficient R is used to judge the reduction of fine particle adhesion powder in the granulation material. It is calculated by the change of 0-3mm fine particles before and after granulation relative to the content of 0-3mm particles before granulation. If the discrimination coefficient R is small, it means that the adhesion effect of 0-3mm fine particles in the mixture is poor, and there are fewer spherical core particles that meet the requirements in the mixture. The change range of fine particles in the falling and drying tests is small. The particle size change in the particle testing process cannot accurately represent the granulation effect. Therefore, it is necessary to use the discrimination coefficient R to distinguish the particle breakage index D and the falling powder loss rate D 落下 And the drying powder removal rate D 干燥 Whether indicators such as these are suitable for evaluating the granulation effect of the mixture.
[0044] The evaluation method for the granulation effect of the sintering mixture provided by the present invention can deeply analyze the particle size distribution state and particle strength of the mixture after granulation, and realize a complete and comprehensive granulation effect evaluation from representative index detection and analysis calculation, thereby driving the high-quality improvement of the granulation effect and improving the output and efficiency of the sintering machine. The evaluation method is relatively complete and targeted, and the evaluation results are highly representative. It can accurately realize the systematic evaluation of the granulation effect of the sintering mixture, and then guide the stability of the mixture granulation system and the adjustment of process parameters, optimize the operation of the sintering system, and finally improve the sintering production efficiency and quality.
[0045] In a specific example, the above granulation is carried out by a drum granulator. The movement of the material in the drum granulator is mainly divided into a climbing stage, a transition stage and a rolling stage. In the cross-sectional direction of the drum, the movement of the particles in the drum granulator is usually divided into six types: sliding, stepping, rolling, small waterfall, large waterfall and centrifugal, such as Figure 1 As shown. The force exerted by the cylinder on the mixture is determined by the linear velocity of the cylinder when it moves. When the cylinder speed is fixed, the larger the cylinder diameter, the greater the linear velocity. Therefore, under the condition of the same cylinder diameter, adjusting the axial length of the cylinder can obtain the same linear velocity when the cylinder moves.
[0046] In order to ensure the effective movement form and effective force of the sintering mixture inside the cylindrical granulator, the cylindrical granulator with fixed size parameters has an appropriate dosage range. When the amount of sintering mixture is small, the filling rate inside the cylindrical granulator is low. Usually, the granulation effect in this scenario is much better than the sintering mixture under the same conditions. The test results at this time cannot accurately reflect the actual granulation effect of the sintering mixture. When the amount of sintering mixture is large, the excessively high filling rate will change the movement form of the particles and the force, making it difficult to ensure that the sintering mixture achieves a better granulation effect.
[0047] At present, the sintering granulation experiment and the evaluation of the granulation effect are usually carried out to meet the needs of the next sintering experiment. The amount of sintering mixture required is large. When the conventional granulation index evaluation is carried out, the sample taken is only a small part of the total granulation material, and the sampling is not representative enough. When only the granulation performance of the sintering mixture needs to be evaluated, it is necessary to set up the mixture with the same sintering amount for granulation experiment. The experimental workload is huge, and it is difficult to achieve a separate evaluation of the granulation effect of the mixture.
[0048] So, in a specific example, Figure 2 As shown, a circular baffle 12 capable of moving in the axial direction of the cylinder 11 is provided inside the cylinder 11 of the cylindrical granulator 10, the outer diameter of the circular baffle 12 is consistent with the inner diameter of the cylinder 11, the inner diameter of the circular baffle 12 is 25% to 33% (e.g., 30%) of the outer diameter, and a granulation space is provided between one side of the circular baffle 12 and the cylinder 11, and the sintered mixture 20 is added to the granulation space for granulation. In this way, by adding the circular baffle 12 inside the cylindrical granulator 10, the diameter of the cylinder 11 can be kept unchanged while adjusting the axial length of the cylinder 11, thereby ensuring an effective particle movement form and effectively reducing the amount of sintered mixture. In addition, when the amount of sintering mixture is low, the samples taken for testing account for a larger proportion of the total sintering mixture, and even the entire sintering mixture can be taken for testing. Under the condition of not changing the granulation effect, the test results that can accurately reflect the granulation effect of the sintering mixture with a lower amount can be obtained, which greatly reduces the granulation workload and can realize the separate evaluation of the granulation effect of the mixture.
[0049] The cylindrical granulator 10 device has strong applicability, simple operation, and low cost. The annular baffle 12 effectively cuts the length of the cylinder 11 to reduce the amount of sintering mixture, and the granulation effect of the full amount of sintering mixture can be simulated by using less sintering mixture, thereby establishing a more accurate and comprehensive evaluation method for the granulation effect of the sintering mixture. The diameter of the annular baffle 12 is adjusted according to the inner diameter of the cylindrical granulator 10, and it can be applicable to cylindrical granulators 10 of various sizes, including but not limited to different models of cylindrical granulators 10 in laboratory and industrial production practice.
[0050] In a specific example, the following steps are also included before granulation: the size of the granulation space is adjusted by moving the annular baffle 12 along the axial direction of the cylinder 11, and the amount of sintering mixture added is adjusted according to the size of the granulation space. By adjusting the position of the annular baffle 12, the effective granulation length of the cylinder 11 can be adjusted without changing the effective diameter of the cylinder 11. After selecting the appropriate amount of sintering mixture, the effective volume of the granulation space is calculated by adjusting the effective granulation length, thereby meeting the requirements of the filling rate of the cylindrical granulator 10 for different amounts of sintering mixture.
[0051] In a specific example, the diameter of the cylinder 11 is 400 mm to 1000 mm, and the length is 700 mm to 3000 mm, but it is not limited thereto and can be adjusted as needed.
[0052] In a specific example, if Figure 3 As shown, three sets of fixing bolts 121 are provided perpendicular to the surface of the annular baffle 12, and the annular baffle 12 is fixed inside the cylinder 11 by screwing the sleeve screw 122 with a handle inside the fixing bolt 121. It can be understood that the fixing method is not limited to this, and other conventional methods can be selected as needed.
[0053] In a specific example, the drop test includes the following steps: taking a portion of the granulated sintered mixture, dropping it from a 2m high pipe (such as a PVC pipe) onto a 10mm thick steel plate, and repeating the drop more than 3 times. In this way, the process of the sintered mixture from the shuttle distributor to the silo, from the silo to the round roller distributor, and from the round roller distributor to the reflector can be simulated.
[0054] In a specific example, the drying test includes the following steps: taking a portion of the granulated sintered mixture, drying it at a preset furnace temperature and a preset wind speed for a preset time, for example, drying it at a furnace temperature of 300° C. and a wind speed of 1.4 m / s for 2 minutes.
[0055] In a specific example, the particle size composition test includes the following steps: taking a portion of the sintered mixture, sieving it with a set of sieves consisting of 8 mm, 5 mm, 3 mm, 1 mm, and 0.5 mm, and then weighing it according to the particle size, and calculating the mass percentage of each particle size. Preferably, the test can be repeated more than 3 times, and the final result is the average value.
[0056] In a specific example, the average particle size is calculated as:
[0057] In a specific example, the sintering mixture is an iron ore sintering mixture, but is not limited thereto, and other sintering mixtures may be selected as needed.
[0058] The present invention will be further described in detail below mainly in conjunction with specific implementation modes and drawings.
[0059] Granulation moisture is one of the important factors affecting the granulation of sintering mixtures. Appropriate granulation moisture can make the particles fully absorb water and generate sufficient capillary force between the adhering powders, thereby resisting the friction between the granulation balls and the shear stress when colliding with the cylinder, which is conducive to the growth of the granulation balls. When the moisture content in the sintering raw materials is low, the particle size of the quasi-particles produced is small and the air permeability of the material layer is poor; when the moisture content is high, the fine particles are almost all attached to the large particles, and the quasi-particles are prone to plastic deformation, forming irregular clumps. At the same time, the material layer is over-humidified, which will also reduce the air permeability. Therefore, exploring the appropriate granulation moisture range of the raw materials is very helpful to strengthen granulation and improve the air permeability of the material layer.
[0060] Bulk density is related to particle size and particle size composition, particle shape and surface state, and is used to evaluate the mass of bulk materials piled per unit volume in a natural state. The permeability index is used to evaluate the permeability of the original material layer of sintered granular materials. The particle size composition and average particle size of particles are basic indicators for evaluating the distribution of fine particles and coarse particles in the mixture. They can characterize the proportion of adhered powder, core particles and intermediate particles in the mixture, and are directly related to the permeability of the mixture.
[0061] Comparative Example 1
[0062] This comparative example was carried out in a cylindrical granulator with a diameter of 700 mm and a length of 1400 mm, and no partition was added inside the cylinder. The total weight of the test mixture was 70 kg each time. The granulation time and the speed of the cylindrical granulator were unchanged (specifically, the granulation time was 5 min, and the speed of the cylindrical granulator was 30 r / min). The effect of granulation moisture on the granulation effect of the iron ore mixture was studied, and the results are shown in Tables 1 and 2.
[0063] Table 1 Comparative Example 1 Effect of granulation moisture on granulation performance
[0064]
[0065]
[0066] Table 2 Comparative Example 1 Granulation Performance Evaluation
[0067]
[0068] It can be seen from Table 1 that with the increase of granulation moisture, the bulk density and permeability index of the mixture both show an upward trend, the permeability index meets the requirements of the sintering experiment, and the average particle size after granulation increases to varying degrees compared with that before granulation.
[0069] As shown in Table 2, under the appropriate granulation moisture, the particle growth index G is relatively high, the content of the +3mm part after granulation increases with the increase of moisture, and the particle distribution index U 3-8The higher the value, the higher the air permeability index of the mixture. Under the condition of low granulation moisture, the discrimination coefficient R≤0.21, the particle breakage index D, the falling powder loss rate D 落下 And the drying powder removal rate D 干燥 It is not suitable for evaluating the granulation effect, which means that the adhesion of the adhesive powder on the core particles is less under the condition of low moisture content, and the granulation effect is poorer than that of the appropriate granulation moisture content. In the range of granulation moisture content of 7.83% to 8.75%, as the granulation moisture content increases, the discrimination coefficient R meets the requirements, the particle breakage index D shows a downward trend, and the powder loss rate D 落下 It showed a trend of first rising and then falling, and the drying powder removal rate D 干燥 When the granulation moisture reaches 8.75%, the drying powder removal rate of the mixture is as high as 17.03%, indicating that too high moisture will lead to poor thermal shock resistance of the mixture. In order to meet the granulation effect and air permeability indicators of the mixture and ensure the strength of the mixture, the granulation moisture should not be too low or too high. In summary, the evaluation of the appropriate granulation moisture of the mixture is between 7.83% and 8.26%, with the middle value of 8.0%.
[0070] Example 1
[0071] This example was carried out in a cylindrical granulator with a diameter of 700 mm and a length of 1400 mm. The effective length of the cylindrical granulator was adjusted to 100 mm by a partition. The total weight of the mixture in each test was 5 kg. The granulation time and the speed of the cylindrical granulator were kept constant. The effect of granulation moisture on the granulation effect of the iron ore mixture was studied. The results are shown in Tables 3 and 4.
[0072] Table 3 Effect of granulation moisture on granulation performance in Example 1
[0073]
[0074] Table 4 Evaluation of granulation performance of Example 1
[0075]
[0076] It can be seen from Table 3 that with the increase of granulation moisture, the bulk density and permeability index of the mixture both show an upward trend, the permeability index meets the requirements of the sintering experiment, and the average particle size after granulation increases to varying degrees compared with that before granulation.
[0077] As shown in Table 4, with the increase of granulation moisture, the particle growth index G first increases and then decreases. The content of the +3mm part after granulation increases with the increase of moisture. The particle distribution index U 3-8 The higher the value, the higher the air permeability index of the mixture. Under the condition of low granulation moisture, the discrimination coefficient R = 0.14, which is quite different from 0.21. At this time, the particle breakage index D and the falling powder loss rate D 落下 And the drying powder removal rate D 干燥The deviation is not suitable for evaluating the granulation effect, which means that the adhesion of the adhesive powder on the core particles is less under the condition of low moisture content. Compared with the appropriate granulation moisture content, the granulation effect is poor. As the granulation moisture content increases, the adhesion of the adhesive powder on the core particles increases, resulting in an increase in the proportion of adhesive powder falling off from the core particles during subsequent transportation and sintering temperature rise. In the granulation moisture range of 7.96% to 8.97%, the discrimination coefficient R meets the requirements. As the granulation moisture content increases, the particle breakage index D shows a downward trend, and the falling powder rate D 落下 And drying powder removal rate D 干燥 All of them showed a trend of first decreasing and then increasing, especially when the granulation moisture reached 8.97%, the drying powder removal rate of the mixture was as high as 28.39%, indicating that under too low moisture, the impact strength of the mixture was poor, while too high moisture would lead to poor thermal shock resistance of the mixture. In summary, the appropriate granulation moisture for the mixture was evaluated to be between 7.96% and 8.39%, and the middle value of 8.2% was selected.
[0078] Conventional granulation was performed using the optimal moisture conditions of Control Example 1, Example 1 and the traditional evaluation method, respectively. The subsequent sintering test results are shown in Tables 5, 6 and 7.
[0079] Table 5 Comparison of sintering indexes under different granulation moisture
[0080]
[0081] Table 6 Effect of granulation moisture on sintered ore particle size composition / mm
[0082] Granulation moisture +40 25-40 16-25 10-16 5-10 3-5 -3 Average particle size 8.0% 11.49 23.71 24.89 12.61 14.30 5.00 8.01 20.55 8.2% 10.26 21.16 27.95 11.81 16.03 4.92 7.87 19.88 8.75% 5.66 17.20 24.96 15.33 19.91 6.65 10.29 17.03
[0083] Table 7 Effect of granulation moisture on the chemical composition of sintered ore / %
[0084] Granulation moisture TFe <![CDATA[SiO2]]> CaO MgO S P <![CDATA[Al2O3]]> 8.0 56.34 5.29 10.19 2.41 0.016 0.072 2.18 8.2 56.75 5.32 10.16 2.36 0.016 0.074 2.17 8.75 56.66 5.30 10.19 2.39 0.016 0.072 2.19
[0085] It can be seen from Tables 5 to 7 that the sintering experiment was carried out based on the optimal granulation moisture evaluated in Example 1 and Comparative Example 1. The sintering utilization coefficient of Example 1 increased from 1.42t / (m 2 ·h) increased to 1.58t / (m 2h), the yield rate and drum strength decreased slightly, the total iron grade of sintered ore increased from 56.34% to 56.75%, and the other sintering indicators and the particle size composition and chemical composition of the sintered ore were close to those of the control example 1, indicating that it is effective to adjust the effective length of the drum granulator by the partition to simulate the granulation effect of the complete drum granulator with less sintering material dosage, and it can accurately reflect the actual granulation effect of the sintered mixture, while the optimal moisture condition of the traditional evaluation method cannot obtain the optimal granulation effect and sintering index. In summary, the evaluation method of the granulation effect of the sintered mixture provided by the present invention has a good application effect, can more accurately evaluate the granulation effect, predict the quality of the sintered ore, and reduce the experimental workload and experimental materials.
[0086] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for evaluating the granulation effect of a sintering mixture, characterized in that: The following steps are involved: Provide a sintering mixture, detect the particle size composition of the sintering mixture before granulation, and calculate the average particle size AS0 before granulation according to the particle size composition before granulation; the particle size composition includes a mass percentage M of a particle size greater than 8 mm +8 , mass percentage of 5~8 mm particle size M 5-8 , mass percentage of 3~5 mm particle size M 3-5 , mass percentage of 1~3 mm particle size M 1-3 , mass percentage of 0.5~1 mm particle size M 0.5-1 And the mass percentage of particle size less than 0.5 mm M -0.5 ; The sintered mixture is granulated, the particle size composition of the sintered mixture after granulation is detected, and the average particle size AS1 after granulation is calculated according to the particle size composition after granulation; According to the formula Obtain the particle growth index G of the sintering mixture according to the formula Get the particle distribution index U of the sintering mixture 3-8 ; The granulated sintered mixture is subjected to a drop test and a drying test respectively, the particle size composition of the sintered mixture after the drop test and the particle size composition after the drying test are detected, and the average particle size AS3 after the drop test is calculated according to the particle size composition after the drop test; According to the formula Obtain the particle breakage index D of the sintered mixture according to the formula Get the powder loss rate D of the sintering mixture 落下 , according to the formula Get the drying powder removal rate D of the sintering mixture 干燥 ; According to the formula Get the discrimination coefficient R; if R≤0.21, it means that the granulation effect is poor, the particle breakage index D, the falling powder rate D 落下 And the drying powder removal rate D 干燥 Not suitable for evaluating granulation effect; if R>0.21, the particle growth index G and particle distribution index U 3-8 Positively correlated with the granulation effect, particle breakage index D, falling powder loss rate D 落下 , Drying powder removal rate D 干燥 Negatively correlated with granulation effect.
2. The evaluation method according to claim 1, characterized in that: The granulation is carried out using a drum granulator.
3. The evaluation method according to claim 2, characterized in that: A circular baffle plate capable of moving along the axial direction of the cylinder is provided in the cylinder of the cylindrical granulator, the outer diameter of the circular baffle plate is consistent with the inner diameter of the cylinder, the inner diameter of the circular baffle plate is 25% to 33% of the outer diameter, and a granulation space is provided between one side of the circular baffle plate and the cylinder.
4. The evaluation method according to claim 3, characterized in that: The method also includes the following steps before granulation: adjusting the size of the granulation space by moving the annular baffle along the axial direction of the cylinder, and adjusting the amount of sintering mixture added according to the size of the granulation space.
5. The evaluation method according to claim 3, characterized in that: The diameter of the cylinder is 400 mm to 1000 mm, and the length is 700 mm to 3000 mm.
6. The evaluation method according to claim 1, characterized in that The drop test comprises the following steps: taking the granulated sintered mixture, dropping it from a pipe at a height of 2 m onto a steel plate with a thickness of 10 mm, and repeating the dropping for more than 3 times.
7. The evaluation method according to claim 1, characterized in that: The drying test comprises the following steps: taking the granulated sintered mixture and drying it for a preset time at a preset furnace temperature and a preset wind speed.
8. The evaluation method according to claim 1, characterized in that The detection of the particle size composition comprises the following steps: Take the sintering mixture and sieve it with a set of sieves consisting of 8 mm, 5 mm, 3 mm, 1 mm, and 0.5 mm. Then weigh them according to the particle size and calculate the mass percentage of each particle size.
9. The evaluation method according to claim 1, characterized in that The calculation formula of the average particle size is: .
10. The evaluation method according to claim 1, characterized in that: The sintering mixture is an iron ore sintering mixture.
Citation Information
Patent Citations
Preparation method of high-chromium vanadium-titanium sintered mixed pellet material
CN104630451A
Production of sintered ore
JP1999092834A